2023
DOI: 10.1007/s11469-023-01146-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Age, and Smartphone Addiction Across 41 Countries

Jay A. Olson,
Dasha A. Sandra,
Samuel P. L. Veissière
et al.

Abstract: JO acknowledges funding from le Fonds de recherche du Québec -Santé (FRQS) and the Canadian Institutes of Health Research. DS acknowledges funding from le Fonds de recherche du Québec -Société et culture (FRQSC). JO, DS, SV, and EL declare that they have no conflict of interest.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
3
1
Order By: Relevance
“…This might be a result of the psychological maturity difference between males and females, with females being more psychologically developed, typically more psychologically resilient than males, and possessing more coping mechanisms. In contrast to the majority of earlier studies, no gender difference was found in the respondents’ levels of internet addiction [ 20 , 55 , 56 , 71 ]. This may be caused by the different problematic internet use behaviors among males and females.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This might be a result of the psychological maturity difference between males and females, with females being more psychologically developed, typically more psychologically resilient than males, and possessing more coping mechanisms. In contrast to the majority of earlier studies, no gender difference was found in the respondents’ levels of internet addiction [ 20 , 55 , 56 , 71 ]. This may be caused by the different problematic internet use behaviors among males and females.…”
Section: Discussioncontrasting
confidence: 92%
“…Therefore, this study suggests that life satisfaction may mediate between the family parenting style and internet addiction among college students. Furthermore, studies on internet addiction behaviors [ 20 , 21 ], family parenting styles [ 22 ] and life satisfaction [ 23 ], have found gender difference. Therefore, this study will further explore the differing mechanisms of internet addiction among male and female college students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average SAS-SV score was 28.69 (SD = 9.25, range: 10 to 60), similar to a previous study with the same recruiting method and similar demographics (M = 27.61, Olson et al, 2023). The average SAS-1 score was 3.77, corresponding to weak agreement (SD = 1.45, range: 1 to 6).…”
Section: Resultssupporting
confidence: 79%
“…Despite the initially proposed six factors underlying the original 33-item scale, a recent analysis found that it has a unidimensional structure (Li et al, 2023). Similarly, a principal component analysis of the largest global survey using the 10-item version of the scale (Olson et al, 2023) shows that one component explains 40% of the variation. Here, we accordingly assessed a single-item version of the Smartphone Addiction Scale.…”
mentioning
confidence: 97%